Strong Metal Phosphide–Phosphate Support Interaction for Enhanced Non‐Noble Metal Catalysis. Issue 5 (21st December 2021) - Chen, Zemin; Zeng, Xiang; Li, Xinyu; Lv, Zhenxing; Li, Jiong; Zhang, Ying
Abstract: Strong metal‐support interaction (SMSI) is crucial for supported catalysts in heterogeneous catalysis. Here is the first report on strong metal phosphide‐phosphate support interaction (SMPSI). The key to SMPSI is the activation of P species on the support, which leads to simultaneous generation of metal phosphide nanoparticles (NPs) and core–shell nanostructures formed by support migration onto the NPs. The encapsulation state of metal phosphide and charge transfer are identical to those of classical SMSIs and can be optimally regulated. Furthermore, the strong interactions of Co2 PL /MnP‐3 not only significantly enhance the anti‐oxidation and anti‐acid capability of non‐noble metal but also exhibit excellent catalytic activity and stability toward hydrogenating a wide range of compounds into value‐added fine chemicals with 100% selectivity, which is even better than Pd/C and Pt/C. The SMPSI construction can be generally extended to other systems such as Ni2 PL /Mn3 (PO4 )2, Co2 PL /LaPO4, and CoPL /CePO4 . This study provides a new approach for the rational design of advanced non‐noble metal catalysts and introduce a novel paradigm for the strong interaction between NPs and support. Abstract : Strong metal support interaction (SMSI) is crucial for heterogeneous catalysis but limited by reducible oxide supports and the activity and stability contradiction. A new strong metal phosphide–phosphate support interaction (SMPSI) induced by P activation is reported for the non‐noble metal catalyst with superior hydrogenation activity, stability, anti‐oxidant and anti‐acid capacity.